Acute coronary vasospasm in a patient with eosinophilic granulomatosis with polyangiitis following NSAID administration: A case report. Issue 47 (November 2016) - Benallegue, Naïl; Lozach, Pierre; Belizna, Cristina; Lavigne, Christian; Urbanski, Geoffrey
Abstract : Abstract: Eosinophilic with polyangiitis (EGPA, formerly known as Churg-Strauss syndrome) is a rare systemic disease characterized by a small-vessel necrotizing vasculitis. Cardiac manifestations are broad-ranging and are associated with a poor prognosis. Coronary vasospasm is uncommon. Here, we report a case of an acute coronary vasospasm in a patient with EGPA after corticosteroids withdrawal and nonsteroidal antiinflammatory drug (NSAID) introduction. This patient was initially misdiagnosed as bradykinin-mediated angioedema. A 30-year-old man presented with recurrence of abdominal pain and acute dyspnea. NSAID administration for pain during a flare was followed by coronary vasospasms leading to cardiac arrest. Corticosteroid treatment was recently interrupted by the patient. This case reports a rare cardiac complication of EGPA. NSAID might contribute to coronary vasospasm by eosinophilic degranulation in EGPA. Moreover, corticosteroid compliance must be emphasized among patients who display EGPA with high cardiac risk to prevent fatal issues.